2016
DOI: 10.3390/w8120586
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Organic Framework-Functionalized Alumina Membranes for Vacuum Membrane Distillation

Abstract: Nature-mimetic hydrophobic membranes with high wetting resistance have been designed for seawater desalination via vacuum membrane distillation (VMD) in this study. This is achieved through molecular engineering of metal-organic framework (MOF)-functionalized alumina surfaces. A two-step synthetic strategy was invented to design the hydrophobic membranes: (1) to intergrow MOF crystals on the alumina tube substrate and (2) to introduce perfluoro molecules onto the MOF functionalized membrane surface. With the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 60 publications
2
28
0
Order By: Relevance
“…The effect of hydrothermal growth hours of MIL‐53 on morphology of M‐ X was investigated (Figure ). Results showed that the surface morphology as well as hydrophilicity of the substrates can be controlled by tuning the MOF growth process, which can also be verified by previous research . The seed particles with small size are evenly distributed on the surface of the support due to the connection between H 2 BDC and Al on the substrate surface (Figure S9, Supporting Information).…”
supporting
confidence: 80%
“…The effect of hydrothermal growth hours of MIL‐53 on morphology of M‐ X was investigated (Figure ). Results showed that the surface morphology as well as hydrophilicity of the substrates can be controlled by tuning the MOF growth process, which can also be verified by previous research . The seed particles with small size are evenly distributed on the surface of the support due to the connection between H 2 BDC and Al on the substrate surface (Figure S9, Supporting Information).…”
supporting
confidence: 80%
“…They do not contain cholesterols, proteins, channels, or a cytoskeleton. So, when a local strain is induced in the membrane of a liposome or exosome, the molecules of the membrane quickly reorganize themselves to reduce this strain, and the membrane rupture is avoided . While in case of an actual cell, a similar strain might cause membrane breakdown or formation of pores on the membrane.…”
Section: Governing Equations For Electrodeformation Phenomenamentioning
confidence: 99%
“…Since all membranes were prepared from the same material, the difference in the surface morphology can thus be held responsible for the change in surface CA values, as can be seen in Table 2 and Figure 1. It is known that highly hydrophobic surface is a result of the presence of multi-scale surface features consisting of both micro-and nano-scale roughness [7,[15][16][17], also known as the lotus leaf effect. The high contact angle on the surface of a lotus leaf is a consequence of such micro-and nano-scale roughness, the micro-and nano-scale roughness can be clearly seen in our case for VIPS-60% and VIPS-80% SEM images, Figure 1.…”
Section: Membrane Morphologies In Nips Vs Vipsmentioning
confidence: 99%